Perilaku Menyontek menggunakan Aplikasi ChatGPT pada Mahasiswa Ditinjau dari Fear of Failure dan Konformitas Teman Sebaya - Jelita, Arfinda Berlian; Kawuryan, Fajar (Universitas Nusantara PGRI Kediri, 2026)
This study aims to examine the relationship between fear of failure and peer conformity with cheating behavior using ChatGPT among university students. The respondents consisted of 125 students selected through purposive sampling. Three types of scale instruments were used in this study: a cheating behavior scale, a fear of failure scale, and a peer conformity scale. The correlation coefficient among the three variables showed a significance value of p = 0.000 (p < 0.05) with an Rx₁₂y value of 0.650, indicating a highly significant relationship between fear of failure and peer conformity with cheating behavior. Thus, the major hypothesis stating that there is a relationship between fear of failure and peer conformity with cheating behavior was accepted, with an effective contribution of 42.2%. The analysis between cheating behavior and fear of failure showed a correlation coefficient Rx₁y of 0.355 with a p-value of 0.000 (p < 0.01), indicating a highly significant positive relationship between fear of failure and cheating behavior. Furthermore, the analysis between cheating behavior and peer conformity showed a correlation coefficient Rx₂y of 0.617 with a p-value of 0.000 (p < 0.01), indicating a highly significant positive relationship between peer conformity and cheating behavior.